Using multiple tracers and geological techniques to determine the connectivity between aquifer systems, West Coast, South Africa. (October 2020) - Van der Schyff, M.; Kanyerere, T.; Israel, S.; Vermaak, N.
Abstract: Langebaan Road and Elandsfontein aquifer found in the West Coast of South Africa was used as the case study. Previous studies on groundwater excluded focusing on ideal methods used to determine aquifer connectivity which is the focus on the current study. Aquifer connectivity in this case study is vital as there are human activities and ecosystems which are proved to be groundwater dependent. Aquifer-aquifer interaction refers to the hydraulic connection between the two aquifers. Factors affecting aquifer connectivity are well known, however appropriate techniques to establish the extent of connectivity remain poorly understood and hence the need to employ various techniques so that the extent of connectivity between the two aquifers is established. A quantitative approach was taken where hydrogeochemical and geological mapping techniques were used to produce a detailed geological conceptual model to describe the groundwater flow direction and aquifer leakage was highlighted. Results showed that Langebaan and Elandsfontein aquifer units have similar chemical signatures with pH ranging from 7.4 to 8.2, EC values ranging from 47 to 379 mS/m, and temperature between 24.6 °C and 28.0 °C. Stable isotope signatures δ 18 O vs δ 2 H showed a mixing between confined and unconfined aquifers. Frequency VLF and magnetometer techniques indicated the presence of geological structures that formed preferential groundwater pathways. Results confirmed the lower aquifer units were linked vertically at site-specific and laterally at the confined units. The vertical leakage between the aquifers through the clay layer was more apparent in some areas compared to others. The study has shown that hydrochemical and geophysical techniques seem appropriate techniques to show the connectivity between aquifer units in the groundwater system. Only two techniques were used, the study recommends using a range of techniques in establishing the interaction between aquifer units in a groundwater system. Highlights: Results showed geological information and conservative tracers were successfully integrated to delineate groundwater flow. Stable isotope δ 18 O-δ 2 H data revealed clear mixing between groundwater from the confined and unconfined aquifer. Groundwater quality is affected by the extent of aquifer-aquifer interaction. The use of stable isotopes, C 14 and geological profiling led to acceptable results to assess aquifer-aquifer connectivity. Groundwater conceptual model showing aquifer-aquifer connectivity was achieved.